Chemical composition and in vitro nutritional assessment of watermelon (Citrullus lanatus) plant silage as a forage option for Murciano-Granadina goats. - Zaira Pardo; Juan Manuel Palma-Hidalgo; Alberto Manuel Sánchez-García; A Ignacio Martín-García (PLoS ONE)
Climate change is exerting significant negative impacts on various sectors, with livestock farming being particularly affected. One of the most pressing challenges in this context is the growing shortage in the availability of conventional fodder. This scarcity has intensified the search for alternative feed sources, with particular interest in underutilized resources often considered waste due to limited knowledge of their nutritional value. This study aimed to assess whether watermelon plant silage (WPS) could be used as a forage source in ruminants. The chemical composition of WPS and alfalfa hay (AH) was analyzed. Results showed similar protein content (21.1 vs. 18.9 g CP/100 g DM, respectively), with WPS exhibiting higher crude fat content (3.16 vs. 1.29 g/100 g DM) but lower hemicellulose (9.95 vs. 14.6 g/100 g DM) and cellulose (20.0 vs. 26.8 g/100 g DM) content compared to AH. In the first in vitro trial, WPS and AH were incubated independently to compare their fermentation behavior. WPS produced a higher concentration of short chain fatty acids (SCFA) (65.9 vs. 61.0 mM; P = 0.304), lower proportions of propionate (P = 0.001), and higher proportions of isobutyrate (P = 0.001). In a second in vitro trial, a formulated goat diet (commercial concentrate and AH in a 1:1 ratio) was used as a control to assess the impact of replacing 25% and 50% of AH with WPS. Trends towards higher value were observed in pH and CH4 concentration as AH was replaced by WPS. The study concluded that WPS could serve as a viable fodder to replace AH in conventional goat diets, simultaneously reducing agricultural waste and serving as a regenerative model for implementing circular economy strategies in affected agronomic sectors.